2018
DOI: 10.1001/jamaoto.2017.3089
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Knowledge of Human Papillomavirus–Positive Head and Neck Cancer

Abstract: Millions of Americans are infected with human papillomavirus (HPV), with rates of HPV-positive head and neck cancer (HNC) expected to surpass cervical cancer by 2020. 1 Nevertheless, most adults are not aware of associations between HPV and HNC. 2 Although debate surrounds HPV vaccine efficacy against these cancers, one trial demonstrated that the vaccine prevents 93.3% of prevalent oral HPV infections. 3 This has the potential to reduce HNC burden if paired with high vaccine uptake, but only 60% of US teens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 7 publications
(9 reference statements)
1
23
0
Order By: Relevance
“…Lack of HPV knowledge in addition to unawareness about the link of HPV with oral/oropharyngeal cancer was seen in recent survey studies with suggested interventional measures including interactive workshops for preclinical students and team-based learning. 20,21,34,35 A recent study that surveyed medical and non-medical students from Ukraine showed a poor level of knowledge regarding HPV-related oral and rectal cancers among all groups of students. 36 Another recent study that surveyed female college students from China, reported similar defect in knowledge about the ability of HPV to cause oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lack of HPV knowledge in addition to unawareness about the link of HPV with oral/oropharyngeal cancer was seen in recent survey studies with suggested interventional measures including interactive workshops for preclinical students and team-based learning. 20,21,34,35 A recent study that surveyed medical and non-medical students from Ukraine showed a poor level of knowledge regarding HPV-related oral and rectal cancers among all groups of students. 36 Another recent study that surveyed female college students from China, reported similar defect in knowledge about the ability of HPV to cause oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…17,19 Medical students constitute a significant group to be targeted with focused knowledge on specific subjects, including the screening and identification of HPV-related premalignant lesions. 20,21 As future physicians, medical students must be aware of the association between HPV and cancer (e.g., cervical and oropharyngeal cancer), in addition to the need for improved knowledge about HPV. 22,23 Consequently, this knowledge could result in a significant impact on patients' survival through the detection of the premalignant lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This invaluable training must start at medical school to alter future career habits. Studies suggest that most pediatricians do not routinely discuss HPV-positive HNC owing to a self-reported lack of knowledge [ 11 ]. Hence, it becomes imperative to examine how we are training our next generation of physicians regarding this epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Due to this epidemiologic shift, HPV-associated head and neck cancer is predicted to exceed the rates of cervical cancer by 2020. 12…”
mentioning
confidence: 99%